(untitled) (Conference on English Language Teaching, 2023)
This study examined students and teacher’s utterance which applied coordinate bilingualism during learning in trilingual school. From that situation, their utterances were analyzed the errors during conversation in a classroom. Moreover, the coordinate situation was also being elaborated regarding social dimensions that occurred in a classroom: social relations between participants, status relations between participants, background and formality, and language functions. The data source used were students who were from mixed marriage families that speak different languages and non-mixed marriage of one and the same language in the tenth grade at CHIS school Denpasar. This school was categorized as National Plus School which is the languages are taught is that Indonesian, English, Balinese, and Mandarin. The participatory observation, questionnaire, and in-depth interview were used to collect data. Purposive sampling method was selected in this study. The data was analyzed qualitatively and also presented informally and descriptively. The result showed that omission and mis-formation mostly appeared when the students responded the teacher’s question and the teacher appeared omission and addition. Most of the students and teacher never did mis-ordering during speaking. Then, social relation more often happened than status relation during learning process.